TELEMEDICINE SERVICES OF THE INDIVIDUAL HEALTH RIGHTS IN NEW NORMAL ERA - Rospita Adelina Siregar (Jurnal Hukum dan Peradilan, 2021)
Regarding the right to protect and respect individual rights as stated in positive law in Indonesia, these rights are part of the human rights of every citizen. So that the state is obliged to guarantee the availability and fulfillment of these rights, in order to avoid the threat of abuse and violations by various parties, including state officials themselves. During the Covid-19 pandemic the question is how can the right to individual health be obtained and the state can guarantee it? This research uses sociological normative juridical research by conducting a survey of 531 respondents in Jakarta in March 2020. The results of the study were analyzed qualitatively so that the state has the authority to guarantee telemedicine services as a form of state responsibility in the new normal era according to Regulation of the Minister of Health of the Republic of Indonesia Number 20 2019 concerning the Implementation of Telemedicine Services between Health Service Facilities.